Pengaruh Harga, Produk, Promosi Dan Lokasi Terhadap Keputusan Pembelian Tanah Kavling De Villa Burning - Elisa Elisa; Mohammad Rizal; Abdullah Syakur Novianto (UNIVERSITAS ISLAM MALANG, 2023)
Abstract The purpose of this research is to identify and analyze the relationship between price, product, promotion and location in purchasing decisions at De Villa Buring. This study uses primary and secondary data collection methods, primary data collection methods in the form of questionnaires by distributing questionnaires to the Buyers of De Villa Buring Plots of Land located in Kedungkandang, Malang City.Determining the number of samples in this study used non-probability sampling using a Likert scale and the results obtained were 90 respondents. Hypothesis testing was carried out using Instrument Test, Normality tests, multiple linear regression tests, and certainty tests. The result of the joint test (F-test) is Variable prices, products, promotions, and location all have a significant positive impact on purchasing decisions at De Villa Buring. In addition, partial test (t-test) results indicate that the price and advertising variables should not partially influence purchase decisions. Product and location variables have a positive and sometimes significant impact on purchasing decisions. This is shown by the judgment test results variations or changes in Purchase decisions can be explained by the variables price, product, promotion, and location. The rest are influenced by other variables not included in the study. We recommend that the De Villa Buring Manager evaluate prices and promotions to further improve them by setting the same prices at each outlet and always updating promotions, especially on Instagram social media. Keywords: Price, Product, Promotion, Location and Purchase Decision